Immunogenicity after CoronaVac vaccination - Güzel,Eda Çelik (2021)
SUMMARY OBJECTIVE: This study aimed to investigate the seropositivity of CoronaVac-SinoVac vaccination in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) risk factors and comorbidities. METHODS: Immunoglobulin (IgG) antibody responses were examined on the 21st day after the second dose of CoronaVac-SinoVac 6 μg vaccine on the 28th day. SARS-CoV-2 IgG antibody levels were measured by using the enzyme-linked immunosorbent assay method in vaccinated health care workers (n=134) (Group I), vaccinated polymerase chain reaction (PCR) (+) who had coronavirus-19 (COVID-19) disease (n=21) (Group II), and unvaccinated PCR (+) (n=28) (Group III) participants. Subgroups were formed in Group I according to the presence of COVID-19 risk factors and comorbidities (diabetes mellitus, cardiovascular disease, and asthma/allergy) and demographic data. RESULTS: Seropositivity rates were 95.5, 100, and 89.3% for Groups I, II, and III, respectively. IgG antibody levels were found significantly higher in the group between the ages of 20–30 in group I compared to those aged 31–50 and over 50 (both p<0.01). It was found significantly higher in normal-weight individuals than in the overweight and obese group (both p<0.01). IgG antibody levels were found significantly lower in people with cardiovascular disease and diabetes mellitus compared with those who did not (p<0.05 and p<0.001, respectively). There was a negative correlation between IgG antibody response values and body mass index and age in Group I (r= −0.336, p<0.001 and r= −0.307, p<0.001, respectively). CONCLUSION: IgG antibody values decrease with age and with increasing body mass index. The presence of comorbidities (i.e., diabetes mellitus and cardiovascular disease) decreased COVID-19 IgG antibody values.